Development Of An Integrated Decision Support System (IDS Online) For An Effective Disease Surveillance And Disaster Management - G.ANTONY RAJ; DR.S.VINCENT; M.MUTHUMARIAPPAN (International Journal of Pharma and Bio Sciences, 2011)
Emerging infectious diseases are a significant burden on global economies and public health. Their emergence is thought to be driven largely by socio-economic, environmental and ecological factor. These diseases have caused devastating effects internationally, with millions infected and billions spent. Some diseases have become pandemic, spreading from one continent to another causing massive mortality rates and affecting global economies and livelihoods. Presently there is no integrated Information System available in the Public Space for recording, analyzing and reporting on Emerging Diseases. IDS ONLINE will meet the need for effectively managing the emerging infectious disease by providing a detailed demographic profile on the incidence of infectious diseases. This initiative will bridge the gap between the actual scenarios at the field level and the decision making process at the management level. Also the Research data so available will be useful for healthcare professionals and researchers for further research and effective management of future outbreaks. The IDS ONLINE System will act as an Effective Reporting Mechanism which will aid in Disaster management.